Competencies Increase the Value of Job Seekers: a Case for Fresh Graduates - Istikomah, Kartini; Suhartono, Suahrtono; Wahyudi, Widi (Sekolah Tinggi Manajemen IPMI, 2024)
The purpose of this study was to determine the direct and indirect effects of formal education and salary variables on time looking for jobs with competence as the intervening variable. This study uses prime data in the form of questionnaires which are distributed to fresh graduate students who have gotten jobs. This study used the intervening regression method with R Studio software to process the data. The research results formal education cannot directly affect the competence of fresh graduate students and can indirectly influence formal education through competence on time looking for jobs. Meanwhile, salary can affect competence directly and have an indirect effect between salary through competence on time looking for fresh graduate student jobs.